2022
DOI: 10.3390/ijerph19148462
|View full text |Cite
|
Sign up to set email alerts
|

Using the Soft Systems Methodology to Link Healthcare and Long-Term Care Delivery Systems: A Case Study of Community Policy Coordinator Activities in Japan

Abstract: Due to the rapidly aging population in Japan, the government has been attempting to link the healthcare delivery system with the long-term care delivery system. However, there are complex challenges that must be overcome to link the two systems. A new methodology should be used to organize complex community challenges and propose solutions. This study aimed to visualize the unique challenges and worldviews of interested parties in each community, using the soft systems methodology (SSM). We aimed to visualize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Smyth and Checkland [6], that to be able to elaborate on the complexity of the problem in this paper, steps in the Soft System Methodology (SSM) are used). In SSM there is a way of elaborating stakeholders in each activity [7]. Warren et al [8] has also explained that the soft system methodology approach makes it possible to describe complex and dynamic issues from various perspectives to become clearer problems to be analyzed in decision making.…”
Section: Methodsmentioning
confidence: 99%
“…Smyth and Checkland [6], that to be able to elaborate on the complexity of the problem in this paper, steps in the Soft System Methodology (SSM) are used). In SSM there is a way of elaborating stakeholders in each activity [7]. Warren et al [8] has also explained that the soft system methodology approach makes it possible to describe complex and dynamic issues from various perspectives to become clearer problems to be analyzed in decision making.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, it is crucial to communicate goals, identify problems, and reach consensus through conversation to enable professionals with different specializations, such as medical and nursing care, to work together as a team [ 25 ]. Therefore, the authors integrated the issues related to multiple Japanese professional collaboration and team formations with the SDM concept; this concept was then considered by the research group while developing the Group’s SDM measure.…”
Section: Methodsmentioning
confidence: 99%
“…A scoping review on the use and outcomes of SSM in healthcare conducted by Augustsson et al [ 78 ] revealed that SSM had most often been used to understand and structure a problem situation and to suggest potential improvements to the situation, but to a lesser extent to implement and evaluate these improvements. For instance, SSM has been adopted to explore patients’ and clinicians’ experience of a specialist epilepsy service delivery and improve it [ 79 ] and to explore radiology staff experience to address the problem situation of heavy workloads [ 80 ]; Goto [ 81 ] used SSM to summarize the current situation of healthcare and long-term care delivery systems, clarify issues and challenges associated with linking these two systems, and propose solutions. Kettlewell et al [ 82 ] applied SSM to study rehabilitation pathways and identify service gap and critical issues.…”
Section: Introductionmentioning
confidence: 99%